Pengaruh Financial Attitude, Financial Knowledge, dan Financial Self-Efficacy terhadap Keputusan Investasi: (Studi Kasus pada Mahasiswa Universitas Indonesia Membangun) - Aprilia, Elsa; Kosadi, Ferry (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to describe investment decisions, financial attitude, financial knowledge, and financial self-efficacy, as well as to analyze the influence of financial attitude, financial knowledge, and financial self-efficacy on the investment decisions of students at Universitas Indonesia Membangun. Utilizing a quantitative method with a descriptive and verification approach, a sample of 96 respondents was selected through purposive sampling, with data collected via questionnaires. The analysis was conducted using multiple linear regression. Descriptive results indicate that the investment decisions, financial attitude, financial knowledge, and financial self-efficacy of Universitas Indonesia Membangun students are categorized as high. Partially, financial attitude, financial knowledge, and financial self-efficacy positively and significantly affect investment decisions. Simultaneously, these three variables have a positive and significant influence on investment decisions, with a correlation of 0.821 and a contribution of 67.4%.